Nandrolone androgenic hormone presents genotoxic effects in different cells of mice - Carmo, Carolina Almeida do [UNESP]; Martini Goncalves, Alvaro Luiz [UNESP]; Salvadori, Daisy Maria Favero [UNESP]; Maistro, Edson Luis [UNESP] (Wiley-Blackwell, 2012)
Nandrolone is an androgenicanabolic steroid (AAS) with diverse medical applications but taken indiscriminately by some to rapidly increase muscle mass. The aim of this study was to evaluate the genotoxic and clastogenic potential of nandrolone (deca-durabolin (R)) in vivo in different cells of mice, using the comet assay and micronucleus test, respectively. The animals received subcutaneous injection of the three doses of the steroid (1.0, 2.5 and 5.0?mg kg-1 body weight). Cytotoxicity was assessed by scoring 200 consecutive total polychromatic (PCE) and normochromatic (NCE) erythrocytes (PCENCE ratio). The results showed a significant dose-related increase in the frequency of DNA damage in leukocytes, liver, bone marrow, brain and testicle cells at the three tested doses and a significant increase of the micronucleated polychromatic erythrocytes at all tested doses. Under our experimental conditions, the nandrolone steroid hormone showed genotoxic and clastogenic effects when administered subcutaneously to mice. Copyright (c) 2011 John Wiley & Sons, Ltd.
Keywords: nandrolone; deca-durabolin (R); clastogenicity; genotoxicity; micronucleus test; comet assay